The Perceived Instrumental Effects of Maltreatment in Sport (PIEMS) scale: Translation, (cross-)validation, and short-form development of the German version - Laurie Schwab; Philipp Röthlin; Roberta Antonini Philippe; Stephan Horvath (Bern Open Publishing, 2024)
Introduction Beliefs about the instrumental effects of maltreatment are a factor explaining abuse in sports. The availability of a valid and reliable German scale measuring these beliefs is essential for a better understanding of the concept. This article introduces and validates the German version of the Perceived Instrumental Effects of Maltreatment in Sport scale (PIEMS-G-14). Methods Study 1 examines the translation and evaluation of the scale structure, the development of a short version (PIEMS-G-6), and both the full and short versions' construct validity and reliability in a sample of youth sports coaches (n = 628). Studies 2 (n = 444) and 3 (n = 423) focus on cross-validating the structure of the PIEMS-G-14 and PIEMS-G-6 in two independent samples of youth sports coaches and provide further evidence of the construct validity and reliability of the scales. Results Despite a reduction in the number of items compared to the original instrument, the PIEMS-G-14 exhibited robust measurement capabilities. The PIEMS-G-6, also demonstrated promising psychometric properties in assessing coaches' beliefs about the instrumental effects of maltreatment. The reliability and validity of both the PIEMS-G-14 and PIEMS-G-6 were further supported by rigorous examination with two independent samples, providing compelling evidence of their construct validity. Discussion/Conclusion The PIEMS-G-14 and PIEMS-G-6 are suitable for use in assessing beliefs about the instrumental effects of maltreatment in German-speaking sports contexts.